2014
DOI: 10.1158/1078-0432.ccr-13-3049
|View full text |Cite
|
Sign up to set email alerts
|

A Signature Predicting Poor Prognosis in Gastric and Ovarian Cancer Represents a Coordinated Macrophage and Stromal Response

Abstract: Purpose: Gene-expression profiling has revolutionized the way we think about cancer and confers the ability to observe the synchronous expression of thousands of genes. The use of putative genome-level expression profiles has allowed biologists to observe the complex interactions of genes that constitute recognized biologic pathways. We used gastric and ovarian datasets to identify gene-expression signatures and determine any functional significance.Experimental Design: Microarray data of 94-tumor and 45-benig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 52 publications
3
55
0
Order By: Relevance
“…Several studies have now confirmed that GCs with a high stromal content, determined either by gene expression analysis or histopathological evaluation, are associated with poor prognosis. 129,130 Similar findings have also been reported in other tumor types, such as breast, lung and esophageal cancers. 131,132 The mechanisms underlying the role of the tumor stroma in supporting GC growth are likely multi-factorial, ranging from providing a suitable extracellular matrix to maintain cancer cell growth, active cell-cell interactions via cancer-associated fibroblasts which can secrete growth-stimulatory molecules such as IL-6, and providing a physical barrier inhibiting chemotherapy from reaching target malignant cells.…”
Section: Beyond the Cancer Cell -Contributions From The Tumor Microensupporting
confidence: 83%
“…Several studies have now confirmed that GCs with a high stromal content, determined either by gene expression analysis or histopathological evaluation, are associated with poor prognosis. 129,130 Similar findings have also been reported in other tumor types, such as breast, lung and esophageal cancers. 131,132 The mechanisms underlying the role of the tumor stroma in supporting GC growth are likely multi-factorial, ranging from providing a suitable extracellular matrix to maintain cancer cell growth, active cell-cell interactions via cancer-associated fibroblasts which can secrete growth-stimulatory molecules such as IL-6, and providing a physical barrier inhibiting chemotherapy from reaching target malignant cells.…”
Section: Beyond the Cancer Cell -Contributions From The Tumor Microensupporting
confidence: 83%
“…Busuttil and colleagues [71] identified a “stromal-response” signature in ovarian cancer that is associated with poor survival and enriched for genes encoding inflammatory and extracellular matrix proteins expressed by the tumor-associated stroma. Furthermore, the mesenchymal subtype of ovarian HGSC, characterized by the upregulation of ECM remodeling genes, has the worst clinical outcome of all subtypes [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…We assembled a gastric cancer database using samples measured in three different sources including previously partly published data at the Max Delbrück Center for Molecular Medicine, Berlin, Germany (“Berlin dataset”, published in GEO as GSE22377) [36]; at the Transgenic Oncogenesis and Genomics Section, Laboratory of Cancer Biology and Genetics, National Cancer Institute, Bethesda, Maryland, USA (“Bethesda dataset”, published in GEO as GSE14210) [37]; and at the Peter MacCallum Cancer Centre, Melbourne, Australia (“Melbourne dataset”, published in GEO as GSE51105) [38]. Sample collection, hybridization, and gene expression measurements were described previously.…”
Section: Methodsmentioning
confidence: 99%